Will the High Biodiversity of Eels in the Coral Triangle be Affected by Climate Change?. Issue 1 (June 2021) - Miller, M J; Wouthuyzen, S; Aoyama, J; Sugeha, H Y; Watanabe, S; Kuroki, M; Syahailatua, A; Suharti, S; Hagihara, S; Tantu, F Y; Trianto,; Otake, T; et al.
Abstract: The Indonesian Seas are at the center of the Coral Triangle, which has the highest marine biodiversity in the world, and the region is under threat from climate change. Freshwater habitats in the region have a high number of anguillid eels compared to other regions of the world, but it is more difficult to capture marine eels to assess their biodiversity. Catches of leptocephali from 5 internationally collaborative surveys for eel larvae (leptocephali) in the Coral Triangle have collected about 126-169 species of larvae, which indicates that the Coral Triangle region likely has the highest marine eel biodiversity in the world based on comparisons to similar larval surveys in the Indian, Pacific, and Atlantic oceans (29-107 species). These marine eel species inhabit a wide range of benthic and pelagic habitats, but how they might be affected by climate changes such as ocean warming has not been considered. Anguillid eels in the Coral Triangle region could be affected mainly by changes in rainfall patterns that could affect their freshwater growth stage or their reproductive maturation patterns and migration. Effects on marine eels would depend on the types of habitats where they live, with the least impacts occurring for deep benthic or pelagic species. Marine eels that live in shallow habitats would be most affected if warming seas and coral bleaching reduce the types of prey species they depend on. Based on their possible association with coral reef habitats, eels of the families Muraenidae and Chlopsidae appear to the most likely types of eels to be impacted by changes in community structure resulting from coral bleaching. All leptocephali species live in the ocean surface layer where they feed on marine snow, so warmer ocean temperatures might reduce the amount or quality of marine snow that is available, resulting in lower larval survival rates. Further studies on eel biodiversity and habitat use will provide more insight into the possible loss of endemic species in the Coral Triangle due to climate change, but presently it is unclear how many species of eels may be directly affected by climate change.